Functional Analysis of Polyprenyl Diphosphate Synthase Genes Involved in Plastoquinone and Ubiquinone Biosynthesis in Salvia miltiorrhiza - Liu, Miaomiao; Ma, Yimian; Du, Qing; Hou, Xuemin; Wang, Meizhen; Lu, Shanfa (Frontiers in Plant Science, 2019)
Polyprenyl diphosphate synthase (PPS) plays important roles in the biosynthesis of functionally important plastoquinone (PQ) and ubiquinone (UQ). However, only few plant PPS genes have been functionally characterized. Through genome-wide analysis, two PPS genes, termed SmPPS1 and SmPPS2, were identified from Salvia miltiorrhiza, an economically significant Traditional Chinese Medicine material and an emerging model medicinal plant. SmPPS1 and SmPPS2 belonged to different phylogenetic subgroups of plant trans-long-chain prenyltransferases and exhibited differential tissue expression and circadian rhythmic expression patterns. Computational prediction and transient expression assays showed that SmPPS1 was localized in the chloroplasts, whereas SmPPS2 was mainly localized in the mitochondria. SmPPS2, but not SmPPS1, could functionally complement the coq1 mutation in yeast cells and catalyzed the production of UQ-9 and UQ-10. Consistently, both UQ-9 and UQ-10 were detected in S. miltiorrhiza plants. Overexpression of SmPPS2 caused significant UQ accumulation in S. miltiorrhiza transgenics, whereas down-regulation resulted in decreased UQ content. Differently, SmPPS1 overexpression significantly elevated PQ-9 content in S. miltiorrhiza. Transgenic lines showing a down-regulation of SmPPS1 expression exhibited decreased PQ-9 level, abnormal chloroplast and trichome development, and varied leaf bleaching phenotypes. These results suggest that SmPPS1 is involved in PQ-9 biosynthesis, whereas SmPPS2 is involved in UQ-9 and UQ-10 biosynthesis.